Is there a Latin American agricultural growth pattern? Factor endowments and productivity in the second half of the twentieth century - Miguel Martín-Retortillo; Vicente Pinilla; Jackeline Velazco; Henry Willebald (European Historical Economics Society (EHES), 2019)
In this article we discuss whether there was a single Latin American pattern of agricultural growth between 1950 and 2008. We analyse the sources of growth of agricultural production and productivity in ten Latin American countries. Our results show that the differences between these countries are too strong to establish a single pattern for this region. However, certain common trends may be observed, such as the growing importance of labour productivity to explain agricultural production growth and the increasing importance of TFP to explain agricultural labour productivity growth.
Keywords: N56; Q10; Q11; 330; Latin American Economic History; Latin American Agriculture; Agricultural Productivity; Agricultural Growth; Total Factor Productivity